1997
DOI: 10.1006/viro.1996.8395
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Apoptosis by the African Swine Fever Virus Bcl-2 Homologue: Role of the BH1 Domain

Abstract: The function of the African swine fever virus (ASFV) bcl-2 homologue, gene A179L, in the regulation of apoptosis was investigated using as a model system the human myeloid leukemia cell line K562 induced to die by apoptosis with inhibitors of macromolecular synthesis, a process that is prevented by overexpression of human bcl-2. It is shown that transfection of K562 cells with the ASFV A179L gene protects these cells from apoptotic cell death induced by a combination of cycloheximide and actinomycin D or by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 27 publications
0
65
0
Order By: Relevance
“…Two additional ASFV genes, 5HL and 4CL (also known as A224L) (1,9,44,50), have also been shown to have roles in the maintenance of infected-cell survival. Thus, ASFV encodes multiple genes involved in aspects of maintaining infected-cell survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two additional ASFV genes, 5HL and 4CL (also known as A224L) (1,9,44,50), have also been shown to have roles in the maintenance of infected-cell survival. Thus, ASFV encodes multiple genes involved in aspects of maintaining infected-cell survival.…”
Section: Resultsmentioning
confidence: 99%
“…Virus isolation and titration were done in primary swine macrophage cultures. Virus titers were calculated using the method of Spearman-Karber and expressed as TCID 50 (22). To select rescued virulent viruses, viremic blood (2 ml) was taken from pigs infected with infection-transfection lysates at 7 days postinfection and inoculated into a second group of naïve pigs.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that ASFV induces apoptosis after 13 h in the cell, a time at which viral morphogenesis is well under way (7). It was also shown that several ASFV genes are involved in the inhibition of apoptosis using different mechanisms (34,43,44), thus demonstrating that programmed cell death during ASFV infection is a tightly regulated process in which the action of inducers is balanced by the expression of antiapoptotic genes. However, less information is available on the process of ASFV-induced apoptosis in terms of the cellular pathways and specific proteins involved.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the DNA sequence of the virus has revealed the presence of several genes able to modulate host-virus interactions (59). Among these, A179L, which encodes a 19-kDa protein structurally similar to the members of the Bcl-2/Bax family, and A224L, which encodes a 27-kDa protein homologous to IAP family members, have been shown to inhibit apoptosis (1,34,43,44). It has also been reported that ASFV induces apoptosis in the cell in a postbinding step, during or after virus uncoating, through the activation of caspases (7).…”
mentioning
confidence: 99%
“…As A224L induces, whereas A238L blocks, NF-B activation, this may suggest that the virus requires a low NF-B activity at early times of the viral cycle to avoid immune responses but a high activity at late times, probably to prevent apoptosis. The virus also encodes another apoptosis inhibitor, a Bcl-2-like molecule (25), which is an early protein in the viral cycle that could also act to inhibit programmed cell death at early times after infection.…”
Section: Discussionmentioning
confidence: 99%